1995
DOI: 10.1002/ijc.2910610502
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase plasminogen activator and urokinase plasminogen activator receptor in breast cancer

Abstract: Urokinase plasminogen activator (uPA) is a serine protease involved in cancer invasion and metastasis. uPA mediates its action while attached to a membrane-bound receptor (uPAR). In this investigation we show that uPAR levels correlate with uPA levels in human breast cancers. uPAR levels, however, do not correlate with other components of the plasminogen activator system such as tissue-type plasminogen activator (t-PA), PAI-I or PAI-2. In addition, uPAR levels showed no correlation with tumor size, axillary-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
81
2
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 17 publications
14
81
2
1
Order By: Relevance
“…Our findings with regard to uPA and uPAR overexpression are in agreement with previous studies carried out in other solid tumours which indicate that both factors are also often concomitantly present at the protein level and that the presence of uPA and uPAR may contribute to tumour invasion and tumour spread and thereby to worse prognosis (Del Vecchio et al, 1993;Duggan et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings with regard to uPA and uPAR overexpression are in agreement with previous studies carried out in other solid tumours which indicate that both factors are also often concomitantly present at the protein level and that the presence of uPA and uPAR may contribute to tumour invasion and tumour spread and thereby to worse prognosis (Del Vecchio et al, 1993;Duggan et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…However, only a few studies of colon (Pyke et al, 1991) and ovarian carcinomas (Schmalfeldt et al, 1995) and of breast (Del Vecchio et al, 1993;Duggan et al, 1995) adenocarcinomas have investigated the simultaneous expression of uPA and its receptor, showing that both factors appear to play a role in the process of tumour invasion and metastasis (Dano et al, 1992). Because of the high metastatic and invasive potential of human pancreatic cancer cells, we have analysed in the present study the concomitant expression of uPA and its receptor in human pancreatic adenocarcinomas.…”
mentioning
confidence: 99%
“…In this study, the prognostic value of uPAR in primary breast carcinomas as documented in earlier investigations by Duggan et al (1995). Grøndahl-Hansen et al (1995), Bouchet et al (1999) and Foekens et al (2000) could be confirmed, high levels of uPAR being associated with poor disease outcome.…”
Section: Months Monthssupporting
confidence: 83%
“…Relatively few studies have reported on the clinical relevance of uPAR in human cancer, though elevated levels of uPAR have been shown to predict poor disease outcome in breast cancer as well (Duggan et al, 1995;Bouchet et al, 1999;Foekens et al, 2000). Recently, we evaluated the clinical relevance of uPA, tPA and PAI-1 determined by a newly developed ELISA in cytosolic extracts as well as in corresponding detergent extracts of pellets obtained after ultracentrifugation when preparing the cytosolic fractions (De Witte et al, 1999a, b).…”
mentioning
confidence: 99%
“…enzyme-linked immunosorbent assay uPA, uPA receptor (uPAR), tPA, PAI-I and PAI-2 were all assayed as described previously (Duggan et al, 1995). Briefly, tumours were homogenized in 50 mM Tris buffer (pH 7.4) containing 1 mM monothiolglycerol.…”
mentioning
confidence: 99%